The Potential Factors Influencing Information Security Awareness on Phishing Attacks From Various Industries: A Systematic Literature Review (SLR) - Asfoor, Ayman Hasan; Rahim, Fiza Abdul (International Journal of Engineering and Technology, 2018)
Phishing attack is one of the techniques used by attacker to get private information from Internet banking customers. This study will systematically analyse published research exploring factors that influencing information security awareness on phishing attacks. A total of 150 articles were used in our review a quality criterion was applied on this set of articles, a total of 20 articles were determined for further analysis, and successfully identified eleven factors as being either directly or indirectly related to awareness on phishing attacks. The factors are security concerns, user competence, computer literacy, self-efficacy, neuroticism, openness, response efficacy and years of PC usage. Moreover, studies have also identified the important role played by motivation. In this way, one could group factors relating to awareness on phishing attacks in three major groups including personality traits, motivation and individual differences. This review may be significant in providing useful information on how to understand users’ susceptibility and vulnerability to phishing scams online.